The Cost Effectiveness of Immunoglobulin vs. Hematopoietic Stem Cell Transplantation for CIDP - Burt, Richard K.; Tappenden, Paul; Balabanov, Roumen; Han, Xiaoqiang; Quigley, Kathleen; Snowden, John A.; Sharrack, Basil (Frontiers in Neurology, 2021)
Abstract Background: Intravenous immunoglobulin (IVIG) is effective in the treatment of chronic inflammatory demyelinating polyradiculoneuropathy (CIDP), but some patients remain dependent on its long-term use. Recently, autologous non-myeloablative hematopoietic stem cell transplantation (HSCT) has been reported to be an effective second line therapy. Objectives: To determine the cost effectiveness of IVIG compared to HSCT in patients with chronic CIDP, we collected data on patients with CIDP undergoing HSCT between 2017 and 2019. This was compared with published literature of the costs and efficacy defined by the Inflammatory Neuropathy Cause and Treatment (INCAT) disability score, hand grip strength, Medical Research Council (MRC) sum score, hand grip strength, and SF-36 quality of life of these treatments for CIDP. Methods: Between 2017 and 2019, nineteen patients with chronic CIDP (mean disease treatment duration 6 years) underwent HSCT with mean cost of $108,577 per patient (range $56,327 to $277,119, standard deviation $53,092). In comparison, published cost of IVIG treatment in the USA for an average CIDP patient exceeds $136,000 per year. After HSCT, 80% of patients remain IVIG and immune treatment free for up to 5 years and compared to immunoglobulins had greater improvement in outcome efficacy Recommendations: Given the long-term treatment-free remission following autologous HSCT, it is more cost effective than long-term IVIG treatment in patients with chronic CIDP. However, costs will depend on patient selection, the HSCT regimen, and regional variations. Further analysis of the health economics of HSCT as second line therapy for chronically IVIG dependent CIDP is warranted.